Particularities of COVID-19 infection in chronic hemodialysis patients in Sub-Saharan Africa: experience from Senegal (West Africa) - Yaya, Kane; AW, BA Mamadou; Tall, Lemrabott A; Mohamed, Mah Sidi; Tidiane, Koulibaly CA; Fatou, Ndiaye; Amadou, Gaye Mactar; Maria, Faye; Moustapha, Faye; Mohamed, Seck S; et al. (Journal of Clinical Nephrology, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) appeared in December 2019 in China and has rapidly become a major global health concern. Patients with end-stage renal disease receiving dialysis treatment are very exposed to the SARS-CoV-2 during their frequent visits to healthcare facilities and immune induced by uremia. The aim of our work was to describe the particularity of COVID-19 infection in hemodialysis patients in sub-Saharan Africa and in Ziguinchor, south of Senegal, particularly. To do this, we conducted a monocentric prospective study over a period of 16 months at the Ziguinchor hemodialysis center and compared our results to a study that focuses on the seroprevalence of SARS-CoV-2 in chronic hemodialysis patients. We found a low prevalence of COVID-19 infection while the majority of our patients were in contact with the virus.